Modified nominal group technique: what and how - Islam, Rafikul (The Karol Adamiecki University of Economics in Katowice, 2009)
Continuous improvement in quality of products/services, more often than not, requires implementation of new ideas in the systems. Consequently, generation of good ideas is regarded as a crucial task in quality management. This paper shows how a traditional brainstorming technique can be integrated with the analytic hierarchy process in generating and subsequently prioritizing a large number of ideas. The working of the integrated technique has been shown by means of two exercises: (1) Identifying important factors to improve quality in teaching, and (2) Identifying important factors to improve quality in academic institutions administration. The method can be applied in many similar situations.